The new annotated checklist of the wild bees of Europe (Hymenoptera: Anthophila)—version 2025 - Ghisbain, Guillaume; Rosa, Paolo; Bogusch, Petr; Brau, Thomas; Carion, Frédéric; Manincor, Natasha De; Devalez, Jelle; Dorchin, Achik; Flaminio, Simone; Greil, Henri; Hölzler, Gerald; Hopfenmüller, Sebastian; et al. (Zootaxa, 2025)
We introduce the initial modification to the most recently issued inventory of European wild bees published by Ghisbain & Rosa et al. in 2023. We report new changes and taxonomic acts including: the description of a new species, Panurginus cypricus Hopfenmüller, 2025 sp. nov.; the lectotype designation of Hylaeus subtilis Förster, 1871; the upgrade or resurrection of five subspecies to species rank: Lasioglossum aeneidorsum (Alfken, 1921) stat. rev., Osmia bulgarica Friese, 1923 stat. rev., Seladonia alpina (Alfken, 1907) stat. rev., Seladonia glacialis (Ebmer, 1979) stat. nov., and Seladonia perkinsi (Blüthgen, 1926) stat. rev.; the resurrection of two species from previous synonymy: Hylaeus subtilis Förster, 1871 spec. resurr. and Protosmia mirabilis (Friese, 1899) spec. resurr.; and Hoplitis taurica (Radoszkowski, 1874) is here considered to be a nomen dubium. Finally, the following six new synonymies are proposed: Anthophora larvata Giraud, 1863 syn. nov. of Anthophora fulvipes Eversmann, 1846; Protosmia monstrosa (Pérez, 1895) syn. nov. of Protosmia tiflensis (Morawitz, 1875); the following taxa are all synonyms of Hylaeus subtilis Förster, 1871: Hylaeus nigrifacies Bramson, 1879 syn. nov., Prosopis gracilicornis var. luteifrons Strand, 1909 syn. nov., Prosopis moricella Bischoff, 1954 syn. nov., and Prosopis moricella f. atricallosa Bischoff, 1954 syn. nov. We also report 4 new species for Europe: Andrena immaculata Warncke, 1975, Anthophora bifasciata Fedchenko, 1875, Nomada felici Schwarz, 1977, and Systropha anatolica Warncke, 1977. Ancyla nitida Friese, 1902 replaces the use of the name Ancyla nigricornis Friese, 1902 in Europe. Nomada chrysopyga Morawitz, 1871 replaces the use of the name N. mauritanica Lepeletier, 1841 in Europe. The presence and identity of species belonging to the genus Schmiedeknechtia in Europe is discussed. Seven species were overlooked and are now added to the European list: Andrena pinguis Ariana, Scheuchl, Tadauchi & Gusenleitner, 2009, Clavipanurgus anatolicus (Warncke, 1972), Eucera cressa (Tkalců, 1984), Eucera mavromoustakisi (Tkalců, 1984), Icteranthidium floripetum (Eversmann, 1852), Seladonia pici (Pérez, 1895) and Megachile sanguinipes Morawitz, 1875. Conversely, seven species are excluded from the European list: Halictus constantinensis Strand, 1910, Halictus rufipes (Fabricius, 1793), Hoplitis turcestanica (Dalla Torre, 1896), Hoplitis caucasicola Müller, 2012, Lasioglossum andromeda Ebmer, 1978, Lasioglossum edessae Ebmer, 1974, and Seladonia confusa Smith, 1853. Heriades labiata Pérez, 1895 is confirmed as being described from Europe (Barcelona), and not Algeria as previously thought. We also report taxonomic changes recorded after the publication of the latest European checklist (Ghisbain & Rosa et al. 2023), including: the revaluation of two genera, Acanthonomada Schwarz, 1966 and Eupavlovskia Popov, 1955; the synonymy of the subgenus Royanthidium with the genus Pseudoanthidium, which is the senior synonym; the report of the neotype designation of Tetralonia malvae (Rossi, 1790); 32 new species recently described as new to science; 12 species recently synonymized and ten subspecies upgraded to species rank; seven species recently resurrected from previous synonymy; eight species recently recorded as new for Europe; one species noticed as overlooked in the previous European checklists; six species recently removed from the European list; and other various changes such as transfer of species from one genus or subgenus to another. We provide corrections to 136 names of authors and specific epithets, years of publication, and gender agreements demonstrated to be incorrect for various reasons. Overall, the present work revises the total number of species for Europe sensu IUCN to 2,187.